Variation in polycyclic aromatic hydrocarbons in sediments of shrimp farms - Ashraf, P Muhamed; Radhakrishnan, A G; Pillai, A G Gopalakrishna (Indian Journal of Fisheries, 2011)
Studies were conducted to find the variations of polycyclic aromatic hydrocarbons (PAH) in sediments of shrimp farms. Evaluation of their concentrations in different cropping seasons were studied in scientifically cultured ponds in comparison with that in a natural pond. The total PAH concentration was found to be higher in the scientific system in all cropping seasons. The levels of individual low molecular weight PAHs, i.e. from naphthalene to phenanthrene showed greater values during the juvenile stages that gradually got reduced at the harvest stage. Benzo[a]anthracene was the prominent component among the high molecular weight PAHs which also showed a maximum value during the juvenile stages of cropping. A slight increase in its value was observed in the harvest stage than late juvenile stages in scientific pond, which may probably be due to the addition of excess nutrients. Benzo[b]fluranthene was nondetectable in natural system, while it showed its presence in scientific system. Correlation data revealed that there is a strong positive correlation between organic matter and the levels of total PAHs, whereas negative correlation with clay which implies the minimum capacity of adsorption of PAH by clays.